Deterministic control of ferroelectric polarization by ultrafast laser pulses - Peng Chen; Charles Paillard; Hong Jian Zhao; Jorge Íñiguez; Laurent Bellaiche (Nature Communications, 2022)
Controlling the electric polarization in ferroelectric materials at room temperature is an important aspect in the design of novel ferroelectric-based devices. Simulations of a typical ferroelectric material now provide insights into why and how its ferroelectric polarization can be partially reversed.